2005
DOI: 10.1590/s1415-54192005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Uso do aparelho de Thurow no tratamento da má oclusão esquelética de Classe II

Abstract: O objetivo deste trabalho foi realizar uma revisão de literatura em relação ao tratamento da má oclusão esquelética de Classe II com a utilização do splint maxilar removível associado à tração alta, realçando sua influência no crescimento ósseo e seus benefícios. Através do relato do caso clínico será mostrada a confecção e os efeitos do aparelho de Thurow quando utilizado no período da dentadura mista, para a correção da Classe II esquelética

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The direction of headgear force might be a critical factor in determining the type of facial growth modification resulting from orthopedic headgear therapy Feizbakhsh et al [12] Stress distribution in maxillary first molar periodontium using straight pull headgear with vertical and horizontal tubes: A finite element analysis…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direction of headgear force might be a critical factor in determining the type of facial growth modification resulting from orthopedic headgear therapy Feizbakhsh et al [12] Stress distribution in maxillary first molar periodontium using straight pull headgear with vertical and horizontal tubes: A finite element analysis…”
Section: Resultsmentioning
confidence: 99%
“…Functional appliances have been widely used in the treatment of Class II malocclusion, since the development of the Andresen activator in the 1930s. These devices, such as the activators of Teuscher, Van Beek and Lehman have the purpose of altering mandibular function and mandibular position to transmit forces, for the teeth and skeletal bases De Pauw & Dermaut [11][12][13][14][15][16][17][18][19][20][21][22], Negi & Negi, [23], Singh & Thin [14]. The headgear (HG) appliance is an effective and common treatment for Class II malocclusions, particularly when limitation of maxillary growth and dental movement are both essential, therefore contributing to the correction of the anteroposterior difference between the maxillary and the mandibular dentitions.…”
Section: Introductionmentioning
confidence: 99%
“…Os elásticos extrabucais atuam remodelando o crescimento ósseo, permitindo um melhor desenvolvimento da face. Assim, alguns fatores devem ser rigorosamente observados para que o tratamento com o aparelho extrabucal seja bem sucedido (SHIMIZU et al,2004;SOUZA et al, 2005) como por exemplo, o tipo de puxada, a inclinação, bem como a linha de ação de força, a idade esquelética do paciente, a magnitude de força e o tempo de uso diário do aparelho. Desta maneira, rotações indesejáveis podem ser evitadas, movimentos dentários ou ortopédicos dos maxilares podem ser planejados, bem como influências sobre o plano mandibular e sobre o padrão de crescimento do paciente podem ser monitorados/controlados.…”
Section: Aplicação Clínica Dos Elásticosunclassified
“…It has been reported that the Thurow appliance can be used to decrease the ANB angle, inhibit maxillary horizontal growth, control vertical growth of the maxilla, maintain the mandibular plane angle, move the upper first molars distally, and improve lip relationships. 12 , 13 , 16 - 19 However, these claims have been based on case reports which have not been compared to control groups. Existing case-control studies were not able to distinguish between dentoalveolar and basal changes produced by the appliance because mandibular and, especially, maxillary superimpositions were not performed.…”
Section: Introductionmentioning
confidence: 99%